Analysis of Factors Influencing Modal Sensitivity of the Curved Surface Cam Reduction Mechanism Based on Orthogonal Tests - Gong Qingshan; Sun Daocheng; Chen Ruyun; Jiang Zhigang; Tan Hao (Jixie chuandong)
In order to design the globoidal cam deceleration mechanism with good performance and improve the transmission performance, the working surface equation and conjugate contact equation are deduced based on the space conjugate contact principle. The constant parameters of globoid cam are preprocessed by using Creo software, and the parametric design of globoid cam deceleration mechanism is completed. According to the finite element method, the first six modes of the reducer mechanism are analyzed. The orthogonal experiment method is used to design the experimental scheme. The influence of pressure angle, rotary pitch radius, roller radius and roller width on the sensitivity of the constraint mode of the reducer mechanism is quantitatively analyzed by statistical theory and variance analysis. The results show that the variances of pitch radius and roller radius of turntable are 0.021 and 0.043 respectively, both of which are less than 0.05 and sensitive to the constraint mode of globoidal cam, followed by the pressure angle and the roller width. The results provide a basis for the study of vibration and noise of globoidal cam mechanism design.